TEACHING TO USE IN SCIENCE AND MATHEMATICS PREVIOUSLY ACQUIRED SKILLS - France, Ilze; Namsone, Dace; Čakāne, Līga; Dzērve, Uldis; Vilciņš, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Goal of the research is to analyse how students currently succeed in using basic skills acquired in mathematics, in science and real-life contexts, before new reforms in Latvia for the development of students' competence have been started. Only about 20% of students in the national testing for 9th grade were able to do it. The research analysed students’ papers, results, and study aids, as well as teacher performance in lessons.